The Role of Celebrity CEO in Enhancing Corporate ESG Performance - Chandra, Budi; Krisyadi, Robby; Anita; Jessica (Accounting Department, Faculty of Business and Management, Universitas Internasional Batam, 2024)
This study examines the impact of celebrity CEOs on corporate ESG (Environmental, Social, and Governance) performance in publicly listed manufacturing companies in Indonesia from 2018 to 2022. Leveraging stakeholder and legitimacy theories, the research explores how the public visibility and media influence of celebrity CEOs drive corporate sustainability. A quantitative approach was employed, utilizing regression analysis to test the hypothesis. The findings reveal a significant positive relationship between celebrity CEOs and ESG performance, with high-profile leaders enhancing corporate transparency, accountability, and sustainability practices. The study highlights the theoretical implications by expanding the understanding of celebrity CEOs within corporate governance frameworks and practical implications for policymakers and corporate boards. However, the study is limited to Indonesia's manufacturing sector and a specific timeframe, suggesting the need for further research across diverse industries and regions. The results underscore the importance of leadership visibility in advancing corporate sustainability, offering valuable insights for stakeholders aiming to align corporate strategies with societal expectations.